If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(1 + -8x) = 175 (1 * 7 + -8x * 7) = 175 (7 + -56x) = 175 Solving 7 + -56x = 175 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -56x = 175 + -7 Combine like terms: 7 + -7 = 0 0 + -56x = 175 + -7 -56x = 175 + -7 Combine like terms: 175 + -7 = 168 -56x = 168 Divide each side by '-56'. x = -3 Simplifying x = -3
| x^2+13x+42=6 | | 3x-5=9x-6 | | 6750/10000 | | 3750/10000 | | 6750/10,000=? | | 25x-2.375=10 | | v/6=-5/7 | | -2(x-5)=4*4 | | -23=4h-3 | | -100=x+20 | | 4x^2-21=-3x | | 7(x+2)-12=5(x+2)-12+16 | | 5-(-7)+2(-8)= | | 550-475= | | -5x+18=x+1 | | 9x^3-39x^2-27x+13=0 | | h=-16t^2+70+50 | | 10x+x=33 | | 13x+10x=9 | | 784/26/43 | | 2b+8=3b-2 | | C=19y+41 | | -x-1/2=2 | | 4(2-5y)+16=-76 | | 2x*30*7*100/39 | | 0.7k+1.4k+9.4=-1 | | 2h-1=45 | | K/-4=9 | | -2.6=-0.1p | | 3(2x+8)-x+5(x-x+5)-3x+1=24 | | 2x+9y=-82 | | 10*x^1/3=9 |